Arsenals of Folly : The Making of the Nuclear Arms Race - Rhodes, Richard, 1937- (London Simon and Schuster, 2008)
The riveting secret history of the post-war nuclear arms race and the end of the Cold War, by the Pulitzer-winning author of The Making of the Atomic Bomb.
Include Notes, Bibliography and Index
Keywords: Nuclear weapons -- Arms race -- United States -- Soviet Union